Merry Christmas, baby - Wilson, Teri (Wilson, Teri. Lovestruck, Vermont., 2021)
Now the guardian of her infant cousin Faith, TV producer Candy Cane decides to embrace the Christmas season and reignite her relationship with Lovestruck, Vermont's pediatrician, Dan Manning.